Not just for laughs: the role of the pilot in commissioning Australian television comedy series. Issue 1 (2nd January 2017) - Tofler, Marilyn; Batty, Craig
ABSTRACT: This article examines how the inclusion of a pilot as part of the proposal for a narrative comedy series, which might include the web series as pilot, can increase the chances of the project being commissioned by a television network. It draws on a series of interviews conducted with Australian television comedy writers, producers and commissioners, and funding agencies, about the importance of the pilot in the pitching process. This includes the potential of the pilot to demonstrate style, tone and comedic nuances; to showcase particular performers; and, in the case of the web series, to generate a ready-made audience – all of which might not be possible on the page. The article refers to successfully pitched and piloted Australian narrative comedy series to give context to its findings, including Wilfred, Lowdown, Please Like Me and The Katering Show . By also drawing on the authors' backgrounds as practitioner–academics with experiences in script development and screenwriting, the article aims to provide both theoretical and practice-based insights about the role of the pilot in narrative comedy pitching and commissioning.